E-Government Communication Strategy: An Analysis of Post-Pandemic Community Attitudes and Adoption - Diryo Suparto; Saifudin Saifudin (Syntax Literate, 2022)
This paper aims to investigate the factors that influence e-government adoption. This paper examines the impact of public attitudes on e-government adoption. The sample data used in this study were 126 respondents from 18 Regencys/cities in Central Java. SPSS 25 was used to test the significance of the effect of the independent variable (attitude) on the dependent variable (e-government adoption). SPSS test results show that attitudes positively and significantly affect e-government adoption. Public service providers can predict the behavior of their users through this paper. As for academics, this paper can be used for further research by integrating attitudes as predictors of adoption behavior. Empirically this research helps increase understanding of political communication between government and society through the provision of new technology.